IMPLIKASI PAJAK PENGHASILAN ATAS ROYALTI HAK CIPTA MUSIK DALAM EKONOMI DIGITAL - Pahlevi, Afaf Naufal; Fauzi, Septian Maulana; Hakam, Gilang Akbar El; Aulia, Alfi Muhammad; Najmudin, Nandang; Kholid, Muhammad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
In today’s digital era, the importance of copyright royalties for music cannot be underestimated, especially in a culturally rich and vibrant country like Indonesia. As the digital industry continues to grow, it has brought both opportunities and challenges for artists and creators. Nevertheless, the regulation of taxation on music copyright royalties has become crucial to ensure a fair balance between the state's interest in generating tax revenue and the creators' right to receive proper compensation for their creative work. This study aims to examine the implications of income tax on music royalties within the framework of the digital economy and assess to what extent the current tax policies can provide legal certainty and protection for creative industry players in Indonesia. The method used is qualitative with a normative juridical approach, and data analysis is carried out descriptively-analytically to illustrate the income tax system on music copyright royalties in Indonesia's digital economy. The results show that music copyrights hold economic value that is systematically supported by the digital economy. The digital economy is a convergence of technologies such as artificial intelligence, big data, and service digitalization, which are reshaping market structures, production processes, and consumer behavior. The current taxation scheme is final in nature and does not account for income distribution or production costs, which results in lower net income for songwriters, particularly those categorized as independent musicians. Other issues include the lack of transparency in royalty reports from digital platforms and the complexity of royalty distribution, which involves multiple cross-border stakeholders.